PENGEMBANGAN APLIKASI PELAYANAN ANTRIAN RUMAH SAKIT GATOEL MOJOKERTO BERBASIS ANDROID - Zam Zam Nuruzzaman; Agi Putra Kharisma; Mahardeka Tri Ananta (Jurnal Informatika, 2022)
Health services are one of the important factors for hospitals. Good and bad services provided will affect the image of the hospital itself. Increased activity in a hospital with limited service facilities will result in queues at the outpatient unit. This happened in Gatoel Mojokerto Hospital. Based on survey that has been conducted, there are 80% of hospital visitors who experience a long queue when registering conventionally and 56% have difficulty receiving information on the doctor's practice schedule. Thus, 94% of patients require an online registration application. The purpose of this study is to make an online registration application to solve patient problems. This research uses waterfall method. In requirement analysis there are 11 functional and 2 non-functional requirements. At the design step, includes the design of use case diagrams, use case scenarios, activity diagrams, sequence diagrams, pseudocode, class diagrams, databases, and interfaces. Then at the implementation step, it produces a database implementation and 12 interface. In the testing step, it is 100% valid on black-box and compatibility. The usability test using SUS resulted in a score of 100 for the admin which was classified as grade A with best imaginable adjective ratings and a score of 88.12 for patients who were classified as grade B with adjective ratings excellent.